Pengaruh Profitabilitas, Gender Diversity, Intellectual Capital, Kepemilikan Manajerial, dan Kualitas Audit terhadap Nilai Perusahaan - Annisa Kusuma Putri; Rina Trisnawati (JURNAL ILMIAH EDUNOMIKA, 2024)
The value of the company is the achievement of certain company conditions based on public trust in the company after going through the process of operational activities from the beginning of establishment until now. This study aims to examine the effect of profitability, gender diversity, intellectual capital, managerial ownership, and audit quality on the value of the company. This type of research is quantitative research. The population in this study is all state-owned companies listed on the IDX in 2019-2022, as many as 27 companies. Sample selection using purposive sampling method. The number of samples as many as 13 companies with data analyzed as many as 46 data. The Data used is secondary data derived from the annual financial statements of state-owned companies listed on the IDX in 2019-2022. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that profitability, gender diversity, and managerial ownership do not affect the value of the company, while intellectual capital, and audit quality affect the value of the company.